ROLE OF BAITUL MAL WAT TAMWIL IN GREEN SHELL BUSINESS OF MUARA VILLAGE GUNUNG JATI CIREBON DISTRICT - Chintya, Natsya Dewi; Bakhri, Syaeful; Ghoni, Abdul (Politeknik Siber Cerdika Internasional, 2023)
This study aims to determine the financing at BMT Gunung Jati for the green mussel business in Muara Village, the role of BMT Gunung Jati for the mussel business in Muara Village and what are the opportunities and challenges of Baitul Mal wat Tamwil in developing the green mussel business in Muara Village. The method used is a qualitative method with field research. Data collection is done by observation, interviews, and documentation. The instruments used were observation sheets and interview guidelines. Data analysis was carried out through data reduction, analysis, and concluding. The results of the study show that the existence of BMT Gunung Jati Cirebon is felt to be very helpful for green mussel business actors in Muara Village in increasing micro-businesses owned by the community because the financing from green mussel business actors BMT Gunung Jati Cirebon in Muara Village has begun to be helped to increase their business so that economic income also increased. Green mussel business actors in Muara Village are no longer afraid of a lack of capital to run their businesses. This research has implications for economic development activities and can be used as a reference.